"Meu nome não é mãe" : um estudo dos discursos sobre maternidade no jornalismo feminista da "Revista AzMina" - Makita, Martha Alvarez Lopes (2019)
With the increasing appropriation of digital technologies by social movements, which had its peak in recent years, especially after 2013, feminist publications on the internet appear such as the "AzMina Magazine". The magazine intends to be a space to increase the feminine representativeness and destines two sections to cover topics related to maternity: the editor "Mãezinha comma" and the column "My name is not a mother". However, if on the one hand the linked texts question the norms on maternity imposed by institutions such as the medical power and the State, on the other, we note that there is a kind of delimitation of new norms related to being a mother, with the recovery of chains such as that of naturalistic feminism and the silencing of discourses, especially with regard to the experience of black women. In order to investigate this process, this research aims at analyzing the discursive struggles about maternity in the publication, with emphasis on the discursive discourses and the tools of legitimation of the mediated discourses, being the testimony one of them. For this, the methodology of discourse analysis of French tradition, supported by authors like Eni Orlandi and Maria Aparecida Baccega, is used.